The Role of Countercyclical Monetary Policy - Ireland, Peter N. (Journal of Political Economy, 1996)
When firms set nominal prices in advance, optimal monetary policy insulates aggregate output against shocks to demand. It can do so, however, by following the constant money growth rule advocated by Milton Friedman; it need not respond to the shocks in an actively countercyclical way. In addition, to the extent that output fluctuations are driven by shocks to supply, money growth should be procyclical.